Impact Of Management Functions On Appointment Of Football Referees In Nigeria Premier League - Ajadi Memunat Tunrayo (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study investigated impact of management functions on appointment of football referees in Nigeria premier league. The objectives were to examine the relationship between remuneration, recruitment process on appointment of football referee. Descriptive research design of survey type was adopted. The population for this study comprises of all football referees both active and retired. Purposive sampling techniques were used to select 150 respondents. A researcher structured questionnaire was used to gather information for the study. The instrument was validated by experts and tested for reliability through test retest method using Pearson Product Moment Correlation (PPMC). The administration of instrument was done by the researcher and two trained research assistants. The data collected were analysis using descriptive statistics of percentage to analysed the research questions while inferential statistics of Pearson Product Moment Correlation (PPMC) was used to test the formulated hypotheses set for the study at 0.05 alpha level. The result revealed that there was a significant relationship between remuneration and recruitment processes and appointment of football referees in Nigeria premier league. The study therefore recommends that the recruitment and appointment of the referees should be based on merit and their remuneration should be conform with the FIFA standard